Inovasi dan Pengembangan Potensi Masyarakat Melalui Olahan dan Pemasaran Udang di Desa Tanjung Rejo Kecamatan Percut Sei Tuan : Teori Community Organization/Community Developmen - Mayang Febi Awaliah; Natal Fernando Panjaitan (Lembaga Pengembangan Kinerja Dosen, 2024)
This project research aims to explain the COCD concept for innovation and development provided to village communities in Tanjung Rejo. The method we used was interviews and direct observation in Tanjung Rejo village. The technique we use is direct data analysis and in-depth observation regarding the conditions of the village we want to empower. The results of this research show that the results of the innovation carried out are very influential and have a sustainable impact on the income of local residents as well as exploring the potential and abilities of local residents to be even better than before regarding shrimp food from their shrimp ponds. Based on the results and discussion of the research